Mencari Model Pendidikan Karakter Di Sekolah - Tharaba, M. Fahim (J-MPI (Jurnal Manajemen Pendidikan Islam), 2020)
The focus of this research is looking for a character education model that was developed on the research site (MAN 3 Malang, SMAN 1 Malang and MA Pondok Pesantren An-Nur Malang Regency). The study used a qualitative approach or in the field of education is often called the naturalistic approach with purposif sampling techniques and snowball sampling techniques as well as sampling time (time sampling). The results of this research are as follows: (1) prioritized values in character education i.e. religious character, honest, discipline, hard work, tolerance, independent, love of homeland, democracy, cooperation, creative, taste of Inging Tau, appreciating achievement; (2) Character education models are conducted through integration into the learning activities of each subject; (3) Character Education Model is done through habituation in daily life in school/Madrasah and integration into school management activities/Madrasah; (4) Character education models are conducted through integration with extra-curricular activities on all three research sites; and (5) constraints encountered in the implementation of character education and solution of its resolution on the three research sites, namely in MA An-Nur Bululawang. The position of the attend which is at one Pesantren Foundation, which makes the policy making should always seek approval from the Pesantren. In addition, the time division of activities is also a constraint. While the character education in the MAN 3 Malang is considered as less effective because it can not be converted in real time in the book Raport and lack of monitoring and evaluation, so that the character education is still limited to normative. While the obstacles faced at SMAN 1 Malang in the form of lack of control and support from the student family, so that each child at home back "loose" can not be monitored as done in the Madrasah.